PENGARUH TINGKAT INTELIGENSI (IQ) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI IPS SMAN 4 PARIAMAN PADA MATA PELAJARAN EKONOMI - -, Anita - (Pendidikan Ekonomi, 2014)
This study aims to determine the effect of intelligence level and motivation on learn outcomes of students of class XI Social SMAN 4 Pariaman on Economic subjects.the method used in this study is a survey method, with a total population of 153 students and the number of samples of 111 students. Sampling technique in this study was proportional random sampling and the intelligence level of students learning outcomes i a secondary data abtained from the existing data in school while learnin motivation derived from the results of the questionnaire that had been tested in advance. The analysis used in this study is a descriptive analysis and inductive analysis. The results of this study indicate that the level of intelligence and motivation to learn either prtially or simultaneously positive and significant effect on learnng outcomes of students of class XI Social SMAN 4 Pariaman on Economic subjects. Based on from the acquisition value of F_ (count) 126,391 > F_tabel significant value of 3,08 and 0,000 < = 0,05